Pendampingan Pengetahuan Mesin EDC Pada Pelaku Usaha Di Desa Cimarga Rangkasbitung Kabupaten Lebak Banten - Diana Triwardhani Kodrat Subagiyo; Yuliniar Yuliniar; Lina Aryani (Jurnal Pengabdian Pada Masyarakat, 2022)
ASSISTANCE OF EDC MACHINE KNOWLEDGE ON BUSINESS ACTORS IN CIMARGA RANGKASBITUNG VILLAGE, LEBAK BANTEN REGENCY. This community service aims to provide knowledge as well as assistance regarding EDC machines, namely Electronic Data Capture machines, namely machines as non-cash payment instruments commonly used by business actors, so that consumers can make payments for their needs. cashless purchases. The method used in imparting this knowledge is by lecture. And the participants were very enthusiastic. with this EDC machine, considering they have never used it before and the speaker will be happy to help in the process of submitting this EDC machine to the bank. From their desire to use the EDC machine, it can be seen that the community service that has been carried out by the dose tone team is the result even though the process of the EDC machine is in the hands of business actors and will wait for the next process.